Phonkrathop læ ʻōkāt čhāk māttrakān thāng kānkhā khō̜ng Sahaphāp Yurōp thī song phon tō̜ kānphatthanā sinkhā læ thēknōlōyī khō̜ng Thai : kō̜ranī sưksā māttrakān trūat sō̜p yō̜n klap ʻāhān læ chalāk rō̜ngrō̜i khābō̜n nai phalittaphan ʻāhān - ʻAphinēt ʻŪnākūn (Sathāban Rawāng Prathēt phư̄a Kānkhā læ Kānphatthanā, 2013)
Research study on the impacts and opportunities of EU trade measures on the development of goods and technology in Thailand; case study of food traceability and carbon footprint label.